An Analysis of Students’ Mastery in Using Degrees of Comparison at the 1st Semester of the 10th Grade of SMK PGRI 4 Bandar Lampung in the Academic Year of 2016/2017 - Kurniawan, Iwan; Oktalia, Mentari (English Education: Jurnal Tadris Bahasa Inggris, 2017)
The objective of this research was to describe the mastery of students in using degrees of Comparison of SMK PGRI 4 BandarLampung.The result of the data analysis of students’ mastery in using Degrees of comparison of the 10th grade students of SMK PGRI 4 Bandar Lampung shown that the students’ mastery of 2016/2017 had fair level.